Utilization of marble powder as fine aggregate in mortar mixes. (20th March 2018) - Kabeer, K.I. Syed Ahmed; Vyas, Ashok Kumar
Highlights: Dried marble slurry waste was evaluated as a potential substitute of river sand in mortars. Marble slurry helps reduce required water content to prepare cement sand mortars. Marble slurry hastens the hydration reaction and forms calcium carboaluminates. Abstract: The construction industry has been responsible for plaguing the environment due to ecological imbalance caused during the extraction and production of building materials. To make this production of construction materials cleaner, the dependency on natural resources has to be reduced. With this aim, marble powder which is a waste product generated during cutting and shaping of marble blocks has been evaluated as a replacement of conventional river sand in cement mortars. For this, four different mix proportions of mortars were evaluated in terms of workability, drying shrinkage, compressive strength, bond and adhesive strengths, density, water absorption and dynamic Young's modulus. Results show that mortar mixes with 20% substitution of river sand by marble powder can be used for masonry and rendering purposes. Such mortars have a distinctively dense microstructure which is a consequence of reduced water requirement and formation of superior quality of hydration products. These were confirmed by scanning electron microscope, thermogravimetric analysis and Fourier transform infrared spectroscopy techniques. Hence, by replacing sand to the tune of 20% by marble powder, would enable the construction industry to reduce their dependency on river sand. Additionally, by utilizing this non-biodegradable marble waste as a building material, would reduce the burden on landfills and therefore help the marble stone industry to be more sustainable.